Quy trình tổ chức hoạt động dạy học khám phá có hướng dẫn nội dung “Định lí côsin” (Toán 10) - Nguyễn Ái Quố, Nguyễn Ái Quố; Trần Hoàng Mỹ, Trần Hoàng Mỹ (Tạp chí Giáo dục, 2026)
Discovery learning is a teaching theory introduced by Bruner in the 1960s, based on a constructivist perspective and emphasizing learning through activities and practical experiences. In this approach, guided discovery learning plays a crucial role in helping students acquire knowledge effectively, fostering a spirit of discovery, promoting independent thinking, and developing self-learning abilities. Using theoretical research methods, this paper proposes a six-step process for organizing guided discovery learning activities on the Cosine Theorem (Mathematics 10): Identifying the objectives of the discovery activity; Presenting a practical problem; Developing a system of guiding questions to organize the discovery process; Formulating the Cosine Theorem; Consolidating knowledge; and Applying knowledge to practice. The effectiveness of guided discovery learning depends heavily on the quality of the guiding questions, the ability to anticipate students' cognitive difficulties, and the teacher's skill in coordinating the discovery process. Therefore, in addition to developing procedures, teachers need to pay attention to the classroom context, the differences in students' abilities, and the teaching conditions.